Resistance training improves body composition and increases matrix metalloproteinase 2 activity in biceps and gastrocnemius muscles of diet-induced obese rats (Clinics, 2014)
OBJECTIVE: We investigated the influence of resistance training on body composition and matrix metalloproteinase 2 activity in skeletal muscles of rats fed a high-fat diet. METHODS: Thirty-two Wistar rats were divided into four experimental groups (n = 8/each) according to diet and exercise status: Control (standard diet), Obese Control (high-fat diet), Resistance Training (standard diet) and Obese Resistance Training (high-fat diet) groups. Animals were fed a high-fat diet for 12 weeks to promote excessive weight gain. Resistance Training groups performed 12 weeks of training periods after this period in a vertical ladder three times/week. Fat percentage, fat-free mass and fat mass were assessed using dual-energy Xray absorptiometry, and matrix metalloproteinase 2 activity in biceps and gastrocnemius muscles was analyzed using zymography. RESULTS: Resistance training significantly reduced body and fat masses and fat percentages in both trained groups (p,0.05). The maximal carrying load between trained groups was not different, but relative force was higher in the Resistance Training group (p,0.05). Of note, increased matrix metalloproteinase 2 activity was noted in the tested muscles of both trained groups (p,0.05). CONCLUSION: In conclusion, altered body composition and muscle matrix metalloproteinase 2 activity promoted by excessive weight gain were positively modified by resistance training.